Global, Regional, and National Burden of Chronic Myeloid Leukemia, 1990–2017: A Systematic Analysis for the Global Burden of Disease Study 2017 - Lin, Qingqing; Mao, Liping; Shao, Li; Zhu, Li; Han, Qingmei; Zhu, Honghu; Jin, Jie; You, Liangshun (Frontiers in Oncology, 2020)
Background: With the advent of tyrosine kinase inhibitors (TKIs), the prognosis of chronic myeloid leukemia (CML) seems to have dramatically improved over the last two decades. An accurate information of the global burden of CML is critical for direct health policy and healthcare resource allocation in the era of high-cost TKI therapy. Objective: This study aimed to evaluate the health burden of CML at global, regional, and national levels from 1990 to 2017. Methods: We collected data of CML between 1990 and 2017 from the Global Burden of Disease (GBD) study 2017 including, annual incidence, mortality, and disability-adjusted life-years (DALY), and the corresponding age-standardized rates (ASRs). To summarize the results, countries were categorized by sociodemographic index (SDI) quintiles, and 21 GBD regions. Results: In 2017, an estimated 34,179 [95% Uncertainty Interval (UI), 31516-36714) incident cases of CML were recorded, and 24054 (95%UI, 22233-26072) CML-related deaths were reported worldwide. Both, the age-standardized incidence rate (ASIR), and age-standardized death rate (ASDR) steadily decreased from 1990 to 2017, with EAPCs of -2.39 (95%UI, -8.13~3.71) and -2.74 (95%UI, -9.31~4.31), respectively. The global incidence and mortality of CML in males were higher than that in females. The ASRs varied substantially across regions, with the highest burden in Andean Latin America, Central Sub-Saharan Africa, and Southeast Asia. Besides, the ASRs decreased most obviously in the high-SDI regions compared to non-high-SDI regions. Moreover, the lower the SDI, the higher was the proportion of deaths in the younger age groups. Conclusion: Despite the decreasing trends of ASRs of CML from 1990 to 2017, the health-related burden of CML remains a challenge for the low-SDI regions. These finds highlight that appropriate strategies should be adopted in low-SDI countries to reduce the ASRs of CML.